Service Quality and Student Referral Intentions in Higher Education: The Mediating Role of Student Satisfaction at Islam Syekh-Yusuf University - Salsa Damanik; Sugeng Lubar Prastowo; Yosi Safri Yetmi (PERFECT EDUCATION FAIRY, 2026)
This study examines how five dimensions of service quality—tangibles, reliability, responsiveness, assurance, and empathy—shape student referral intentions through student satisfaction at Islam Syekh-Yusuf University, Indonesia. A sequential exploratory-to-confirmatory design was used: preliminary interviews contextualized service issues and informed the survey, followed by a cross-sectional questionnaire administered to 175 students from the 2021–2022 cohorts selected using proportional random sampling. The structural model was estimated with partial least squares structural equation modeling (PLS-SEM) in SmartPLS 3.2.9. The results show that assurance is the only SERVQUAL dimension with a statistically significant positive effect on student satisfaction (β = .386, p = .003). Student satisfaction, in turn, strongly predicts referral intention (β = .583, p < .001). Assurance also has a significant indirect effect on referral intention through satisfaction (β = .225, p = .005), whereas the other indirect effects are not significant. The model explains 51.7% of the variance in student satisfaction and 72.9% of the variance in referral intention. Internal consistency and convergent validity are acceptable; however, several heterotrait–monotrait (HTMT) ratios exceed the conventional .90 threshold, indicating that discriminant validity is not fully established for some construct pairs. The study therefore supports a focused managerial implication: competence, credibility, security, and clear communication are central to satisfaction-driven student referrals, while the non-significant dimensions should not be interpreted as unimportant without addressing measurement overlap and contextual heterogeneity.